Kapasitas Fiskal, Kebijakan Energi Terbarukan, dan Ketahanan Ekonomi Regional: Studi tentang Transisi Indonesia - Deo Renaldi Saputra; Elinda Novita Dewi; Ni Ketut Sukanti; Sahal Hanafi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Indonesia’s renewable energy transition poses both opportunities and challenges for regional economic resilience. This study examines how fiscal capacity influences the effectiveness of renewable-energy policies and shapes economic outcomes across Indonesian provinces. Provinces with stronger fiscal autonomy are better able to finance green infrastructure, support private investment, and implement adaptive measures that mitigate employment disruptions and market volatility. Regions with limited fiscal resources face challenges in energy diversification and structural adjustment, resulting in uneven resilience. Using a qualitative approach based on official government reports, institutional datasets, and energy-transition statistics, the study analyzes the interactions between fiscal governance, renewable-energy policy, and regional economic adaptation. Findings indicate that fiscal disparities significantly determine investment capacity, policy implementation, and long-term structural transformation. Strengthening fiscal capacity, promoting sustainable finance, and aligning renewable-energy strategies with local development priorities are essential to ensure equitable and resilient economic outcomes. This research contributes to understanding the critical role of fiscal governance in enabling a successful, regionally inclusive energy transition.